2021
DOI: 10.3390/jpm11040241
|View full text |Cite
|
Sign up to set email alerts
|

Forgetting Unwanted Memories: Active Forgetting and Implications for the Development of Psychological Disorders

Abstract: Intrusive memories are a common feature of many psychopathologies, and suppression-induced forgetting of unwanted memories appears as a critical ability to preserve mental health. In recent years, biological and cognitive studies converged in revealing that forgetting is due to active processes. Recent neurobiological studies provide evidence on the active role of main neurotransmitter systems in forgetting, suggesting that the brain actively works to suppress retrieval of unwanted memories. On the cognitive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 270 publications
(372 reference statements)
0
8
0
Order By: Relevance
“…Recent studies in rodents and humans have demonstrated that such memory selection processes do not consist simply in activation of the appropriate memory item but also require the concomitant inhibition of inappropriate but related mnemonic content which may be evoked by the global or local environment and thereby intrude into conscious attention, competing with and perturbing accurate local action choice (M. C. Anderson & Hulbert, 2021;Brewin & Smart, 2005;Wimber et al, 2015). The literature refers to such inhibition of interference as adaptive, directed, or active forgetting (M. C. Anderson & Hulbert, 2021;Tanaka et al, 2019;Costanzi et al, 2021), where this term is to be understood in the organizational and attentional sense of 'Forget about that for a moment' rather than as total erasure of a memory episode. This organizational conception of memory function fits with classical theories and computational models conceiving of cognitive consciousness as a global workspace (GW) of limited capacity (Baars, 1988(Baars, , 1997(Baars, , 2002Dehaene et al, 2003;Dehaene & Changeux, 2011; for a novel distributed neuronal version of the global workspace, or GNW, see Mashour et al, 2020).…”
Section: Active Forgettingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies in rodents and humans have demonstrated that such memory selection processes do not consist simply in activation of the appropriate memory item but also require the concomitant inhibition of inappropriate but related mnemonic content which may be evoked by the global or local environment and thereby intrude into conscious attention, competing with and perturbing accurate local action choice (M. C. Anderson & Hulbert, 2021;Brewin & Smart, 2005;Wimber et al, 2015). The literature refers to such inhibition of interference as adaptive, directed, or active forgetting (M. C. Anderson & Hulbert, 2021;Tanaka et al, 2019;Costanzi et al, 2021), where this term is to be understood in the organizational and attentional sense of 'Forget about that for a moment' rather than as total erasure of a memory episode. This organizational conception of memory function fits with classical theories and computational models conceiving of cognitive consciousness as a global workspace (GW) of limited capacity (Baars, 1988(Baars, , 1997(Baars, , 2002Dehaene et al, 2003;Dehaene & Changeux, 2011; for a novel distributed neuronal version of the global workspace, or GNW, see Mashour et al, 2020).…”
Section: Active Forgettingmentioning
confidence: 99%
“…Our starting point interpretation is that EdM errors increase as a function of trial difficulty primarily as a result of the repeated instances of inhibitory active-and retrieval-induced forgetting (Bekinschtein et al, 2018;Tanaka et al, 2019;Costanzi et al, 2021;M. C. Anderson & Hulbert, 2021; M. C. Anderson et al, 1994) entailed by the continuous mnemonic retrieval and organization the EdM protocol was designed to elicit (Al Abed et al, 2016).…”
Section: Active Forgetting and Everyday-like Memorymentioning
confidence: 99%
“…Moreover, research has shown dynamic interaction between the prefrontal cortex and the temporal gyrus during the process of memory suppression ( Depue et al, 2007 ). Specifically, an increase in brain activation in the DLPFC was found to be accompanied by decreased activity in the hippocampus during memory suppression ( Costanzi et al, 2021 ). These findings indicate that brain regions including the DLPFC, the temporal gyrus and hippocampus play an important roles during memory suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the rate of forgetting is integral to its function. Excessively persistent memories due to slow forgetting, especially those of aversive experience, may be associated with mental health issues in posttraumatic stress disorder ( 8 ). In addition, mutants of several autism-risk genes in Drosophila displayed reduced behavioral flexibility associated with impaired forgetting ( 3 , 9 ).…”
Section: Introductionmentioning
confidence: 99%